The Mediating Effect of Business Performance on the Relationship between Financial Literacy and MSMEs’ Loan Repayment Performance - Oktaviani, Luh Gede Adilia; Sri Werastuti, Desak Nyoman (Dinasti Publisher, 2026)
This study aims to analyze the effect of financial literacy on business performance and its impact on MSMEs’ loan repayment performance in Buleleng Regency. This research employs a quantitative approach with MSMEs in Buleleng Regency as the population, totaling 66,368 business units. The sample was determined using the Slovin formula with a 10% margin of error, resulting in a minimum sample size of 100 MSMEs in Buleleng Regency. The sample was selected using a purposive sampling technique. Data were collected through questionnaires distributed directly to MSME owners. The data collection method utilized a questionnaire measured on a 1-4 Likert scale. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS) with the assistance of SmartPLS version 3 software. The results indicate that financial literacy has a positive effect on business performance and loan repayment performance, business performance has a positive effect on loan repayment performance, and financial literacy influences loan repayment performance through business performance.